Standards for Collection, Preservation, and Transportation of Fecal Samples in TCM Clinical Trials - Wenquan Su; Yawei Du; Fengmei Lian; Hui Wu; Xinrong Zhang; Wenli Yang; Yunfeng Duan; Yuanming Pan; Weijng Liu; Aiming Wu; Bowen Zhao; Chongming Wu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
BackgroundUnlike chemical drugs with a single or a few kinds of active compounds, traditional Chinese medicines (TCMs)uses herbal formulas composed of numerous kinds of chemical constituents. Therefore, TCM clinical trials require unique and stricter standards for collecting, preserving, and transporting fecal samples than those used for chemical drugs. Unfortunately, there are no special standards for processing fecal samples in TCM clinical trials.MethodsWe invited interdisciplinary experts within TCM clinical trials and gut microbiome research to help formulate this standard. After more than a year’s in-depth discussion and amendments, we achieved a standard via expert interviews, literature research, questionnaire surveys, and public opinion solicitation. This standard has been reviewed and approved by the Standards Office of China of the Association of Chinese medicine.ResultsWe established a sample information processing method prior to TCM clinical sample collection, which is adapted to the unique features of TCM. The method formulates detailed processing requirements for TCM information in addition to the factors that may disturb the gut microbiome. We also constructed a set of methods for collecting, preserving, and transporting fecal samples that meet the characteristics of TCM. These methods formulate detailed operating specifications on the collection approaches, storage conditions, transportation requirements, and management of fecal samples.ConclusionsThis standard guides the information processing prior to sample collection and the standard operating procedures for the collection, preservation, and transportation of fecal samples in TCM clinical trials, which also can be used as a reference by clinicians and researchers in modern medicines.